(untitled) (International Journal of Scientific Pediatrics, 2023)
Introduction. In anorectal abnormalities (ARA), immediate surgery is usually required to open the anus for emptying, unless the fistula can be relied upon or until corrective surgery is performed. Depending on the severity of the anomaly, treatment is carried out only by anoplasty of the perineum or colostomy at the first stage and a certain recovery later. Purpose of the work. evaluation of the effectiveness of one-stage correction in the treatment of newborns with recto-vestibular fistula and its comparison with the three-stage method. Material and methods. The study was conducted in the period 2020 to March 2022 at the Andijan Regional Children’s Multidisciplinary Medical Center. As a randomized, single-blind clinical trial, 40 newborn girls with ARA and rectovistibular fistula were included in the study. The control group consisted of 20 newborns who underwent a three-stage operation, the main group consisted of 20 patients who underwent a one-stage correction. Statistical analysis of the data was carried out using the SPSS 16.0 program. The significance level in this study was taken as 0.05. Results. Complications during and after surgery were registered in both groups, and a comparative assessment was carried out. In the control group, only one case (5%) of wound infection and dehiscence was seen, while six cases (30%) were observed in the one-stage operation. With regard to the incidence of other complications, no significant differences were found between the two groups. Conclusions. One-stage rectovestibular fistula repair is the preferred and reliable treatment for patients with non-perforated anus and rectovistibular fistula.